The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1002/asi.4630330107
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration in computational musicology

Abstract: Productivity and collaboration are defined in terms of a 1966 study of a scientific group. These two parameters in a humanistic subject, computational musicology, are compared with the earlier study. The two most collaborative musicologists are also most prolific. However, only IWO of the humanistic literature are involved in coauthorship as compared with 80% of the scientific subject. Although heavy collaboration is an effective mechanism to stimulate substantially higher productivity, there is also a distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 7 publications
1
14
0
3
Order By: Relevance
“…Studies [PRICE & BEAVER, 1966;ZUCKERMAN, 1967;PAO, 1982;DUQUE & AL., 2005;LEE & BOZEMAN, 2005; have emphasised the close relationship between collaboration and publication. Because of the division of work (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Studies [PRICE & BEAVER, 1966;ZUCKERMAN, 1967;PAO, 1982;DUQUE & AL., 2005;LEE & BOZEMAN, 2005; have emphasised the close relationship between collaboration and publication. Because of the division of work (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…This interest originates from the problem raised in collaboration situations: does collaboration leads to a higher productivity (number of papers), cf. earlier studies [BEAVER & ROSEN, 1979;BORDONS & GÓMEZ, 2000;BORGMAN & FURNER, 2002;PAO, 1981;1982;1992;PRICE & BEAVER, 1966;SUBRAMANYAM, 1983;ZUCKERMAN, 1967;. Of course, as described above, we are in a position to study the general performance-productivity relation in general IPPs.…”
Section: Introductionmentioning
confidence: 90%
“…Pao goes on to prove that the global collaborators are much more productive than the local ones. On the other hand, Pao's earlier studies [5,6], for example one in Computational Musicology was found to be a bit inconclusive with respect to collaboration and production mainly due to the different sociological habits of the researchers in Humanities (as compared to those in Sciences). In the same vein, Bordons and Gómez [7] and Subramanyam [8] have commented on some of the above mentioned papers.…”
Section: Introductionmentioning
confidence: 93%